2003
DOI: 10.1034/j.1399-3054.2003.00078.x
|View full text |Cite
|
Sign up to set email alerts
|

Light‐harvesting complex gene expression is controlled by both transcriptional and post‐transcriptional mechanisms during photoacclimation in Chlamydomonas reinhardtii

Abstract: To compensate for increases in photon flux density (PFD), photosynthetic organisms possess mechanisms for reversibly modulating their photosynthetic apparatus to minimize photodamage. The photoacclimation response in Chlamydomonas reinhardtii was assessed following a 10‐fold increase in PFD over 24 h. In addition to a 50% reduction in the amount of chlorophyll and light‐harvesting complexes (LHC) per cell, the expression of genes encoding polypeptides of the light‐harvesting antenna were also affected. The abu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
65
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 76 publications
(102 reference statements)
9
65
0
Order By: Relevance
“…For C. reinhardtii cells grown photoautotrophically, a decrease in Chl content upon exposure to high light was reported before (Neale and Melis, 1986;Durnford et al, 2003;Bonente et al, 2011). Here, we show that this decrease occurs in all conditions upon exposure to high light, independent of the carbon availability.…”
Section: The Acclimation Responses To High Lightsupporting
confidence: 81%
See 1 more Smart Citation
“…For C. reinhardtii cells grown photoautotrophically, a decrease in Chl content upon exposure to high light was reported before (Neale and Melis, 1986;Durnford et al, 2003;Bonente et al, 2011). Here, we show that this decrease occurs in all conditions upon exposure to high light, independent of the carbon availability.…”
Section: The Acclimation Responses To High Lightsupporting
confidence: 81%
“…The gene expression of different LHCs has been reported to be affected by light acclimation (Teramoto et al, 2002;Durnford et al, 2003;Yamano et al, 2008) and to be NAB1 regulated (Mussgnug et al, 2005). It has been observed that longterm high-light exposure of C. reinhardtii cells leads to a 50% decrease of Chl content (Neale and Melis, 1986;Bonente et al, 2012) and to changes in Chl-to-Car ratio (Niyogi et al, 1997a;Baroli et al, 2003;Bonente et al, 2012), suggesting reduction of the antenna size (Neale and Melis, 1986), although, in a more recent report , it was concluded that the antenna size is not modulated by light in this alga.…”
mentioning
confidence: 99%
“…Promising models propose the chloroplast redox state (for review, see Fey et al, 2005) to give rise to retrograde signals from the chloroplast to the nucleus, altering Lhc gene expression. Lhc gene transcript levels have been shown to correlate with protein levels detected (Anandan et al, 1993;Durnford et al, 2003;Ganeteg et al, 2004), but contrasting data have also been reported (Flachmann and Kü hlbrandt, 1995;Flachmann, 1997). Therefore, rising Lhc gene transcript levels alone might not necessarily lead to elevated protein abundance.…”
mentioning
confidence: 99%
“…Thus, it is not surprising that the PQ pool redox state has been identified as a key signal modulating the expression of photosynthesis-related genes in response to light conditions (8). Studies on algae like Dunaliella tertiolecta and Chlamydomonas reinhardtii (9) showed that PQ redox state influences dramatically the expression level of photosynthetic genes. In particular, the largest effects were observed in the genes encoding members of the lhc family, whose expression is strongly repressed upon exposure to strong light.…”
mentioning
confidence: 99%